Pengaruh Kejujuran Transparansi dan Kualitas Pelayanan terhadap Repeat Order pada Grabfood Kota Bengkulu - Indriani Hernisyah Putri; Romi Adetio Setiawan; Syaifuddin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The development of app-based food delivery services is driving increasingly fierce competition, requiring companies to maintain customer trust and satisfaction to increase repeat orders. This study aims to reveal the influence of honesty, transparency, and service quality on repeat orders among GrabFood users in Bengkulu City. The research method used was a quantitative approach with a survey design. Data were collected through questionnaires distributed to GrabFood users in Bengkulu City and then analyzed using multiple linear regression analysis. The results showed an R-Square value of 0.359, indicating that 35.9% of the Repeat Order variable on GrabFood (Y) is influenced by Honesty (X1), Transparency (X2), and Service Quality (X3), while the remainder is influenced by other factors. In conclusion, honesty, transparency and service quality simultaneously have a positive and significant influence on repeat orders on GrabFood because it has a significance value of 0.000 which is smaller than 0.05, but partially only service quality is significant. It is recommended that future research examine other factors that may influence repeat orders, such as price, promotions, or customer satisfaction, which were not examined in this study.